How do Teachers in Training Review their texts? - Antonio García; José Luis Gallego Ortega; Antonio Rodríguez Fuentes (Universidad Autónoma de Baja California, 2015)
In this article, is presented an investigation of writing cognitive process in teaching students from Granada University, following Hayes' model (1996). This is a qualitative investigation, known as a multiple case study. Cognitive interviews are used in order to collect data and content analysis is applied to interpret this data. Results reflect that students consider the review process as an activity of their own. They use a formal review instead of a content review, although, they compare their texts with the initial ideas almost instantly. Students recognize the importance of this activity and assume the necessity to apply it, in spite of their executive deficits.